Determinants of Agricultural Productivity: Analysis of the Welfare of Agrarian Countries - Basri; Ramadhani, Muhammad Akbar; Prasasti, Riska; Atkiyan, Fahrul Hudatil; Baihaqi, M. A Sahal; Wau, Taosige (Jurnal Ilmu Ekonomi Terapan, 2025)
Objective: This study aims to analyze the determinants of agricultural productivity and their impact on the welfare of agricultural countries. Agricultural productivity plays a pivotal role in the economic development of agricultural economies, as their growth largely depends on the performance of the agricultural sub-sector. The research adopts an empirical and quantitative approach to identify the key drivers contributing to productivity enhancement in agriculture. Design/Methods/Approach: The study employs secondary data obtained from reputable sources, including Our World in Data, the World Bank, the Food and Agriculture Organization (FAO), ILOSTAT, and the Economic Research Service. The sample consists of seven countries with the highest agricultural productivity globally, covering the period 2012–2021 based on data availability. The analysis examines the effects of land area, fertilizer consumption, agricultural labor, carbon emissions, and financial development on agricultural productivity. Findings: The results show that land area has a significant negative effect on agricultural productivity, while fertilizer consumption and agricultural labor have significant positive effects. Carbon emissions and financial development exert positive but statistically insignificant effects. These findings suggest that physical inputs and labor remain the main drivers of productivity growth in agricultural economies, whereas environmental and financial factors have yet to exhibit substantial influence. Originality/Value: This study contributes to the literature by comparatively identifying the determinants of agricultural productivity among the world’s most productive agricultural countries. By utilizing cross-country and time-series data, it enriches empirical understanding of how both input and non-input factors shape global agricultural performance, offering insights relevant to food security and sustainable economic development. Practical/Policy implication: The findings provide valuable guidance for policymakers, agricultural practitioners, and stakeholders to promote more efficient agricultural practices through the adoption of modern technologies, improved access to productive inputs such as fertilizers, and capacity-building for agricultural labor. These efforts are crucial to strengthening food security, enhancing farmers’ welfare, and supporting inclusive economic growth in agricultural economies.